A 90-day toxicity and genotoxicity study with high-purity phenylcapsaicin. (10th May 2018) - Paulsen, Torbjørn Rage; Stiller, Sebastian; Weber, Klaus; Donath, Claudia; Schreiband, Gudrun; Jensen, Knut Helge
To evaluate the safety of the synthetic capsaicin analogue phenylcapsaicin (PheCap; 7-phenylhept-6-yne-acid-hydroxy-3-mathoxylbenzylamide, CAS no 848127-67-3), a 90-day repeated dose oral gavage of 0, 30, 100 or 250 mg/kg body weight (bw)/day toxicity study with a 28-day recovery period was conducted using Wistar rats. Examinations of clinical signs, body and organ weight, haematology, urinalysis, clinical chemistry, food consumption and macroscopic, as well as histopathological tissue examinations were carried out for signs of toxicity. Degenerative, but reversible changes in the liver at 250 mg/kg bw/day, and local irritating effects in the stomach at 100 and 250 mg/kg bw/day were found. These findings were associated with test item-related clinical symptoms, that is, diarrhoea, salivation and moving of bedding material. PheCap did neither cause gene mutations by base pair changes or frame shifts in the genome of the tester stains Salmonella typhimurium TA 98, TA 100, TA 1535, TA 1537 or TA 102 nor induce structural and/or numerical chromosomal damage in human lymphocytes. Therefore, it can be concluded that PheCap is not genotoxic. The No Observed Adverse Effect Level (NOAEL) of PheCap for systemic toxicity is considered to be at 100 mg/kg bw/day which is based on degenerative changes in the liver. Due to irritating effects in the stomach, the NOAEL for local effects was established at 30 mg/kg bw/day.